Promoting Student-Run Online Class Review Activities as Effective Cooperative Learning - Ruttanokorn, Kanong; Nuntanakorn, Paiboon; Janmahasatian, Sarayut; Rojanarata, Theerasak (Indian Journal of Pharmaceutical Education and Research, 2020)
Objectives: The aim of this work was to enable students to set up and organize for themselves online review activities after class. Materials and Methods: Students worked as groups to create short notes and quizzes that covered the topics from a lecture course and shared them by using free online tools. To provide support and motivation, the instructors offered advice on how to organize the activities and effectively create quizzes and notes. Prizes were awarded to students who won the popular votes for the best short notes and some students’ quizzes were incorporated into the end of course exam. After the activities, the students’ opinions and levels of satisfaction were surveyed. Results: The students generated, submitted for evaluation, revised and then shared class review materials on a website operated by students themselves. After being improved through instructor’s assessment, the quizzes and short notes were well received and used by students, resulting in a higher average exam score with a lower variance than that in the previous year in which these activities were not conducted. The students reported that they were satisfied with the activities, had a positive attitude towards them and perceived their benefits. Furthermore, they understood the process of how to produce online review activities and were confident that they could transfer their experiences to set up similar activities in other courses. Conclusion: By giving students the opportunity of learning how to run lesson review activities online and providing them with appropriate supports, learning can be shifted from a teacher-organized task to a student-run activity, providing an effective means of cooperative learning.
Keywords: Student-run; Review activity; Online; Quiz; Notes; Cooperative learning